2022
DOI: 10.3389/fimmu.2022.843247
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Proinflammatory Cytokines and T Cells in Patients With Tourette Syndrome: A Meta-Analysis

Abstract: BackgroundTic disorder is a neurodevelopmental disorder characterized by motor and phonic tic symptoms. Tourette syndrome (TS) is a subtype of tic disorder that shows more persistent tic symptoms. The etiological mechanism of TS concerning immune dysfunction remains unclear due to limited evidence, especially for pediatric TS patients.MethodIn the present study, a meta-analysis was performed to confirm the identified changes in proinflammatory cytokines and T cells of pediatric TS patients. A total of five dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Ying Li et al conducted a meta-analysis in 2022 to indicate changes in proinflammatory cytokine patterns and T cells in pediatric patients with Tourette syndrome. They proved an association between peripheral immune system activation and Tourette syndrome [20]. Another study conducted in 2010 has shown that interleukin-2 (IL-2) concentrations are associated with the severity of tic disorders [21].…”
Section: Discussionmentioning
confidence: 98%
“…Ying Li et al conducted a meta-analysis in 2022 to indicate changes in proinflammatory cytokine patterns and T cells in pediatric patients with Tourette syndrome. They proved an association between peripheral immune system activation and Tourette syndrome [20]. Another study conducted in 2010 has shown that interleukin-2 (IL-2) concentrations are associated with the severity of tic disorders [21].…”
Section: Discussionmentioning
confidence: 98%
“…Besides, many cytokines can act as neuromodulators and their expression is strictly regulated at peripheral and central nervous systems by means of neurotransmitters 29 . A recent meta-analysis found elevated levels of increased levels of proin ammatory cytokines in pediatric patients with Tourette syndrome, including TNF-α and IL-6 5 . Consistent with this analysis, we found elevated levels of IL-1β, TNF-α, IL-6 and IL-4 expression among children with TD, while state anxiety among those children correlated positively with IL-17 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the last three decades suggest that immune mechanisms may play a role in the development of TD. For instance, various studies suggest that children with TD may have elevated levels of proin ammatory cytokines such as TNF-α, IL-1β, IL-2, IL-6, IL-8, IL-12, IL-17, and IFN-γ 5 . TD among children was found to be associated with autoimmune disorders such as asthma, allergic rhinitis, allergic conjunctivitis and possibly eczema and food allergies 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Leckman et al also compared tic disorder patients and healthy controls, showing that the patients had elevated IL-12 and TNF-α levels [ 30 ]. A recent meta-analysis summarizing 25 studies also identified small-to-large effect sizes for increased IL-6 levels and a large effect size for increased TNF-α levels in tic disorder patients [ 31 ]. Additionally, although not directly about tic disorders, some studies found that OCD patients, which is comorbid with tic disorder, have increased monocytes compared to healthy controls, which in turn release more cytokines including GM-CSF, IL-1β, IL-6, IL-8, and TNF-α [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%